Link budget analysis for dual sideband optical carrier suppression RoF system - Yaakob, S.; Idrus, Sevia Mahdaliza; Abdul Kadir@Jaafar, Muhammad Zamzuri; Salleh, Mohd Shahril; Mohamad, Romli; Rashidi, C.B.M.; Zan, Zuraidah; Mahdi, Mohd Adzir (IEEE, 2019)
A radio over fibre (RoF) system is designed to be in an integrated fiber-wireless access network using the millimeter-wave (mm-wave) as a wireless transmission carrier. The design employs the dual-sideband optical carrier suppression (DSB-OCS) technique for mm-wave carrier generation purpose. A dual-electrode Mach-Zehnder modulator (DE-MZM) is used in this technique to generate 40 GHz carrier in order to distribute 1.25 Gbps data via direct modulation (DM) over a 20 km RoF system. The link budget shows that Gigabit-per-second (GBps) wireless transmission of 1.4 m distance can be achieved using direct modulation laser diode (DMLD) with the bit error rate (BER) of 10−9 and wireless transmit power of −12.38 dBm. The proposed system is able to upgrade existing passive optical network (PON) system to carry high capacity wireless signal for future high speed GBps distribution system